Application of Tree Regression in Long Study of University of Jember‘s Student Use R Program - Yuliani Setia Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
This research aimed to implemate tree regression with one respon and six explanatory variables in R programand apply it to know variables which distinguish long study of University of Jember’ student. We can use “tree”function to form tree regression in R. The result of research shows that the rate of long study University ofJember’s Student is 1802 days. Based on structure of tree we can know that variables can used to distinguishuniversity of Jember’s students in long study are GPA, time used for doing minithesis and faculty Fromimplementation of tree regression,it is known that tree regression can identify variables locally, revealinteractions in the data set, no variable is assumed to follow any kind of statistical distribution and easy tointerpret. Keywords : tree regression, R program , tree function, long study